Infraestructura y violencia: Reconfiguraciones biopolíticas y democracia en el bicentenario de Costa Rica - Pérez Saborío, Edgar (2023)
The present article reflects on biopolitics of the bicentennial Costa Rica through its infrastructures as Governmentalitysecurity devices. Recent building works such as Circumvallation and the Legislative Parliament are analyzed, concluding the emergence of new forms of violence that hinder the politic manifestation of various populations in urban democratic life of the country.